Neonicotinoid metabolites in farmland surface soils in China based on multiple agricultural influencing factors: A national survey - Hou, Jie; Chen, LiYuan; Wang, JinZe; Wang, LiXi; Han, BingJun; Li, YuJun; Yu, Lu; Liu, WenXin (Journal of hazardous materials, 2025)
Certain neonicotinoid metabolites (mNEOs) are causing widespread concern because they are equally or even more toxic than the parent NEOs. Currently, there is limited information on the distribution of mNEOs in soil. Especially, it is unknown that the effects of agricultural factors, such as plastic filming, plowing, irrigation, and fertilization, on mNEOs. This study is the first to reveal that mNEOs were commonly found in agricultural topsoil in China, with a geometric mean concentration of ΣmNEOs of 0.298 μg/kg. Among 31 provinces in Mainland China, Fujian had the highest mNEO residues, whereas Shanghai had the lowest. Among topsoil of various crop types, that of fruits and vegetables were found the highest mNEO residues. Furthermore, higher levels of film cover were associated with higher mNEO residues. Microplastics (MPs, serving as contaminant carriers) were positively correlated with mNEOs under field conditions, which was related to the adsorption capacity of microplastics and its influence on the soil conditions and the years of film cover. Alternatively, this study shows for the first time that irrigation water and manure might be sources of mNEO input into the soil, and that the plowing frequency might also influence on mNEOs. [Display omitted] •There was at least one mNEO found in 95.7 % of the topsoil of China.•Spatial differences in mNEO residues in topsoil were significant.•Crop type and ploughing frequency significantly affected soil mNEOs.•Multiple perspectives on the effects of film covering and MPs on mNEO residues.•Irrigation water and manure might be input sources for soil mNEOs.